Overtime working in the U. K. - Spink, R. M. (Cranfield University, 1990)
The key objectives for this research were to: () Provide a database in order to extend the knowledge and understanding of the management and use of overtime across the whole economy; ii) Review and test a range of research questions and hypotheses concerning specific problems and controversies surrounding the use of overtime. The research was structured within three main phases viz. desk-research, fieldwork and analysis. The Initial search for Improved U. K labour market management revealed overtime to be a key factor, equivalent to 1.5 million full time jobs, and apparently little understood. It had been forecast that overtime would fall In the late 1970s and 1980s and that this fall would result from the combined effects of: unemployment, uncompetitive unit labour costs and increasing management scrutiny. In the event overtime Increased considerably and continues to increase, confounding many of the soothsayers. In 1988-89, the cost of overtime to employers was £15,000 million, £5,000 million of which was the premium paid to secure the benefits which management must have considered the overtime would bring to their organisations. A research market gap was found regarding the use and management of overtime across the economy as a whole. Moreover, this knowledge would be needed since change remains an apparent inevitability. It was against this backdrop that overtime was investigated. Desk- research was directed at providing an unbounded literature review, addressing the key issues which surround the use of overtime. This review established that there is a high degree of controversy regarding the use of overtime and it facilitated the detailed design of the research questions and hypotheses. A multi-faceted methodology was developed to Investigate these questions and test the hypotheses. This Involved building on the desk-research, using two mutually supportive fieldwork techniques; firstly, a survey, using a mailed questionnaire, and secondly, a set of semi-ethnographic case studies. The Survey covered all economic sectors, sizes of establishment and regions of the U. K. It yielded 225 usable cases, representing over 40,000 employees and collected a wide range of statistical data regarding the use and management of overtime and structures and perceptions of working time. These results were analysed by reference to a number of structural variables, including: sector; regional location; size of establishment; type of worker and overtime levels. The resulting series formed a basis for standardised comparisons between the structural variables. A range of statistical data and significant associations and differences were established, providing a unique empirical database and thereby satisfying one of the key objectives of the research. Thus the survey produced a skeleton of statistical evidence, whereas the case studies built on this framework to give the detailed explanation and Interpretation needed for a better understanding of the processes involved. The results of both the desk-research and fieldwork were drawn together to help resolve the research questions and test the hypotheses. It was established that overtime detracts from operational flexibility, confounding the majority of managers who claimed flexibility-based reasons such as'unexpected demand' and 'emergency cover' as the prime explanations of their use of overtime. Indeed, about 75% of overtime was found to be systematic, insofar ash was predictable, and therefore operated either by management choice or default. The effects of overtime on employment were more significant than had been indicated in the literature. For example, the substitution of overtime for employment was found to be more widespread than most commentators had predicted, although managers did not readily yield to this fact. Conversely, worker dependency on overtime earnings was found to be much less common than previous research had allowed. In concert with the literature, however, dear and extensive evidence was found to associate overtime with ineffective management. A significant amount of overtime was simply unnecessary from an operational viewpoint, and the majority of the balance was ineffective In that it was less cost-effective than the alternatives. Such unnecessary and ineffective overtime was characterised by phenomena such as: mistaken management understanding of its application, effects and comparative costs; an inappropriate management decision process leading to its use; the improper and inadequate utilisation of management controls; employee control of the overtime and adverse employee welfare associated with its use. Notwithstanding the above conclusions, a minority of overtime was found to be an effective and rational means for management to satisfy demand and to meet corporate objectives.